The role of social media instagram community to tourism promotion in Baubau city - Taqwa Utami, Nur (COMMICAST, 2022)
compete in terms of promotion with several other regions. The tourism policy carried out by the local government has not been able to make tourism the main asset of the City of Baubau. This study examines the role of community social media in the tourism promotion of Baubau City, particularly on Instagram social media accounts. The research is focused on Instagram accounts that have tourism content and searches for hashtags that have the most posts about tourist objects. The research method used is descriptive qualitative. Next, to check the validity of the data, what the researchers did was to make previous observations on various relevant Instagram accounts randomly. Then the data that has been obtained is confirmed, described, categorized which is the same view, which is different, and which one is specific from the data sources. Finally, the data were analyzed by researchers to produce conclusions. The analysis technique used by these researchers is the source and content triangulation analysis technique. The results showed that community accounts on Instagram were very helpful in providing promotion for tourism in Baubau City, besides that the popular hashtags used made it easy for the public to get information about content, location, and access to several tourism objects in Baubau City.